Analisis Restitusi Pajak Pertambahan Nilai dan Kenaikan Tarif Pajak Pertambahan Nilai 11 % pada KPP Pratama Palembang Ilir Barat - Yolanda, Maria; Fajriana, Icha (CV. Lafadz Jaya, 2023)
This study aims to determine and analyze the application of value added tax refunds, increases in value added tax rates and the relationship between value added tax refunds and increases in value added tax rates. This research was conducted at the Palembang Ilir Barat Primary Tax Service Office. In this study the research approach used was descriptive and the type of data used was qualitative. Sources of data used in this study are primary and secondary data with data collection techniques including documentation and interviews. The results of this study indicate that KPP Pratama Palembang Ilir Barat in implementing the 11% value added tax refund is in accordance with the provisions of the Directorate General of Taxes.